2010
DOI: 10.1614/ws-09-106.1
|View full text |Cite
|
Sign up to set email alerts
|

The Allelopathic Potential of Kudzu (Pueraria montana)

Abstract: We explored the allelopathic potential of kudzu as a function of its phenolics. Aqueous and methanol extracts of different kudzu organs (leaf, stem, root, and seed) were assayed for allelopathy with the use of lettuce and radish seeds. Both leaf and root extracts significantly inhibited all of the measured germination indices (total germination, speed of germination, and coefficient of the rate of germination) (all P < 0.01). When treated with leaf extract, the total germination of both species was ∼ 20% le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 46 publications
2
21
0
1
Order By: Relevance
“…germination showed that they are the most sensitive index compared to other germination indices for assessing the phytototoxic effect and such type of findings are well documented in other studies (Chiapusio et al 1997;Rashid et al 2010a). In addition, radicle length and biomass were inhibited more than hypocotyl length and biomass parameters, a common finding in phytotoxicity studies (Burgos & Talbert 2000).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…germination showed that they are the most sensitive index compared to other germination indices for assessing the phytototoxic effect and such type of findings are well documented in other studies (Chiapusio et al 1997;Rashid et al 2010a). In addition, radicle length and biomass were inhibited more than hypocotyl length and biomass parameters, a common finding in phytotoxicity studies (Burgos & Talbert 2000).…”
Section: Discussionsupporting
confidence: 71%
“…Some studies report that the extracts of alfalfa, kudzu, and black mustard had inhibitory effects on seed imbibition (Chon et al 2004;Rashid et al 2010a;Tawaha & Turk 2003). Seed imbibition, the first phase of germination, is an important step to germination and if water uptake does not reach a Note: ***, **, * and ns indicate significant difference from control at P 5 0.001, P 5 0.01, P 5 0.05 and non-significant respectively after applying the Dunnett's test.…”
Section: Discussionmentioning
confidence: 99%
“…The results are supported by the findings of Rashid et al (2010), who reported impaired growth of lettuce (Lactuca sativa) and radish (Raphanus sativus) seeds (root and shoot length and fresh weight) by the allelopathic potential of leaf and root leachates of kudzu (Pueraria lobata). Tanveer et al (2008) also reported that minimum GI and germination percentage of rice seeds were observed when such seeds were treated with leaf leachates of Common Cocklebur (Xanthium strumarium).…”
Section: Discussionsupporting
confidence: 85%
“…Although many studies on the allelopathic potential of other legume weeds have been published (Kamo et al, 2003;Rashid et al, 2010), the allelopathy of R. capitata has not yet been evaluated. Rashid et al (2010) concluded that leaf and root leachates of kudzu (Pueraria lobata) have strong allelopathic potential which could impair growth of lettuce (Lactuca sativa) and radish (Raphanus sativus) seeds (root, shoot length and fresh weight).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation